Eocene aposematic patterns persist in modern European Lycidae beetles despite the absence of co-mimics - Motyka, Michal; Kazantsev, Sergey V; Kusy, Dominik; Perkovsky, Evgeny E; Yamamoto, Shûhei; Bocak, Ladislav (iScience, 2023)
Ancient aposematic signals might have evolved under different ecological circumstances. Using European Cenozoic amber and phylogenetic reconstruction, we evaluated the evolution of net-winged beetle aposematism. We describe Priabonian Hiekeolycus winkleri sp. nov. from Baltic amber, review known fossil species, and suggest earlier high diversity and morphological conservativeness of European Lycidae since the Eocene. We hypothesize the presence of red and black/red aposematic patterns in Eocene Europe. The analyses suggest the Oligocene to Miocene dispersal of additional species from East Asia and their advergence to autochthonous patterns. Recently dispersed lycids have retained similarities with their East Asian relatives. Net-winged beetles are rare in Europe after the Quaternary climatic oscillations, and we hypothesize a currently relaxed selection for shared aposematic signals. Neophobia, and eventually inborn rejection of brightly colored prey, putatively preserved ancient aposematism under changing conditions. Evidence from paleontology and phylogenetics can provide insight into the long-term persistence of old adaptations under changing conditions.
Keywords: Evolutionary biology; Zoology; Paleobiology